Differential Forecast of Pornography Addiction: Originating in Shame and Pathological Narcissism - Asem Esmaeili; Kiumars Farahbakhsh; Asia Shariatmadar (پژوهش‌های کاربردی روانشناختی, 2022)
This study aimed to forcast the differentiation of pornography addiction based on feelings of shame and pathological narcissism in Tehran city in Iran. The research approach had a practical aim and correlational data collecting. The population of the study was all men above 18 in Tehran city in 2020-2021. Among them, 200 samples (100 people addicted to pornography and 100 people did not addict to pornography) were selected voluntarily via the internet. The research tools were Pornography Problem Consumption Scale (PPCS), Fear of Guilt and Shame (GASP) Scale, and Narcissism (MTNS) Scale. The discriminant analysis and SPSS-26 software was used for analyzing data. The results demonstrated that the ability to feel shame and pathological narcissism has a positive relation in predicting pornography addiction. They can predict the group membership of men with pornography addiction and without pornography addiction. Moreover, it can be concluded that with the increase of shame and pathological narcissism of people, their use of pornography increases. It can be advised to therapists and counselors who have clinicians exposed to pornography and, more generally, sexually addictive behaviors, pay special attention to the embarrassment and narcissism experienced and the personality type of these individuals.